SORTING NEXIN 1 Functions in Plant Salt Stress Tolerance Through Changes of NO Accumulation by Regulating NO Synthase-Like Activity - Li, Ting-Ting; Liu, Wen-Cheng; Wang, Fang-Fang; Ma, Qi-Bin; Lu, Ying-Tang; Yuan, Ting-Ting (Frontiers in Plant Science, 2018)
Nitric oxide (NO) production via NO synthase (NOS) plays a vital role in plant tolerance to salt stress. However, the factor(s) regulating NOS-like activity in plant salt stress tolerance remains elusive. Here, we show that Arabidopsis SORTING NEXIN 1 (SNX1), which can restore H2O2-induced NO accumulation in yeast Δsnx4 mutant, functions in plant salt stress tolerance. Salt stress induced NO accumulation through promoted NOS-like activity in the wild type, but this induction was repressed in salt-stressed snx1-2 mutant with the mutation of SNX1 because NOS-like activity was inhibited in the mutant. Consistently, snx1-2 displayed reduced tolerance to high salinity with decreased survival rate compared with the wild type, and exogenous treatment with NO donor significantly rescued the hypersensitivity of the mutant to salt stress. In addition, the snx1-2 mutant with reduced NOS-like activity repressed the expression of stress-responsive genes, decreased proline accumulation and anti-oxidant ability compared with wild-type plants when subjected to salt stress. Taken together with our finding that salt induces the expression of SNX1, our results reveal that SNX1 plays a crucial role in plant salt stress tolerance by regulating NOS-like activity and thus NO accumulation.